2011
DOI: 10.1089/jir.2010.0055
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Type I Interferon Rapidly Protects Swine Against Challenge with Multiple Serotypes of Foot-and-Mouth Disease Virus

Abstract: Foot-and-mouth disease virus (FMDV) causes a highly contagious disease of cloven-hoofed animals. Current inactivated vaccines require approximately 7 days to induce protection, but before this time vaccinated animals remain susceptible to disease. Previously, we demonstrated that intramuscular (IM) inoculation of a replication-defective human adenovirus type 5 (Ad5) vector containing a porcine interferon α gene (pIFNα) can protect swine challenged 1 day later by intradermal (ID) injection with FMDV A24 Cruzeir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 25 publications
4
57
0
Order By: Relevance
“…Thus far, we have demonstrated that inoculation of mice with VRP-GFP induced a strong protective antiviral response against FMDV which correlated with increased levels of IFN-␣ in serum. This is in accordance with the demonstrated antiviral and protective effect of type I IFN against FMDV in the natural host (4,9,10). To confirm the antiviral effect of IFN-␣ against FMDV in the mouse model, we treated groups of five mice with 10 4 U of muIFN-␣ followed by challenge with 5 ϫ 10 4 PFU of FMDV A24 at 4 or 18 h after treatment.…”
Section: Ib-rs-2 Cells Do Not Respond To Vrp-gfp Infectionsupporting
confidence: 79%
See 4 more Smart Citations
“…Thus far, we have demonstrated that inoculation of mice with VRP-GFP induced a strong protective antiviral response against FMDV which correlated with increased levels of IFN-␣ in serum. This is in accordance with the demonstrated antiviral and protective effect of type I IFN against FMDV in the natural host (4,9,10). To confirm the antiviral effect of IFN-␣ against FMDV in the mouse model, we treated groups of five mice with 10 4 U of muIFN-␣ followed by challenge with 5 ϫ 10 4 PFU of FMDV A24 at 4 or 18 h after treatment.…”
Section: Ib-rs-2 Cells Do Not Respond To Vrp-gfp Infectionsupporting
confidence: 79%
“…As we previously demonstrated, administration of Ad5-poIFN-␣ sterilely protected swine from FMDV infection (10). Since our results in cell culture indicate that VRPs containing an IFN gene induce an enhanced protective response and higher levels of ISGs than VRP-GFP treatment, we plan to initiate studies in naturally susceptible animals with different doses of VRP-po/ boIFN-␣/␤ and examine their efficacy against FMDV challenge.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations